The Influence of Land Area, Production Costs, Pond Farming Experience and Pond Farmer Groups on Fish Farmers' Income in Pucangtelu Village, Kalitengah District, Lamongan Regency - Ardiansyah, Alfian; Yulistiyono, Herry (Universitas Islam Lamongan, 2024)
This research aims to determine and analyze the partial and simultaneous influence of land area, production costs, pond farming experience, and pond farmer groups on the income of fish farmers in Pucangtelu Village, Kalitengah District, Lamongan Regency. This research uses a quantitative approach by collecting data obtained through structured interviews. The total sample was 90 respondents using the Slovin method. The analysis technique used is multiple linear regression analysis. The results of this research show that the variables of land area and production costs have a positive and significant partial effect on the income of fish farmers, while the variables of pond farming experience and pond farmer groups have no partial effect on the income of fish farmers in Pucangtelu Village, Kalitengah District, Lamongan Regency. Simultaneously, it shows that the variables of land area, production costs, pond farming experience, and pond farmer groups have a significant effect on the income of fish farmers in Pucangtelu Village, Kalitengah District, Lamongan Regency.